Senile cardiac amyloidosis: an underappreciated cause of heart failure. (7th February 2013) - Shah, Shreena; Dungu, Jason; Dubrey, Simon William
Abstract : This case presents a patient with biopsy-proven, wild-type transthyretin (TTR) senile amyloidosis. The case was that of a man in his early 70s who presented with gradually progressive symptoms and signs of heart failure. The recent history included an episode of severe pancreatitis secondary to cholelithiasis and subsequently (and incidentally) noted hepatomegaly and marked ascites. Further evaluation of the aetiology of the heart failure, through echocardiography, coronary angiography and endomyocardial biopsy, led to an exact diagnosis of SSA. The patient is being treated with conventional heart failure medications while consideration is given to the use of diflusinal as an antiamyloidogenic small molecular stabiliser of TTR. Monitoring and further management advice are being coordinated by the National Amyloidosis Centre.